If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5 + -1x = -6x Solving 5 + -1x = -6x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '6x' to each side of the equation. 5 + -1x + 6x = -6x + 6x Combine like terms: -1x + 6x = 5x 5 + 5x = -6x + 6x Combine like terms: -6x + 6x = 0 5 + 5x = 0 Add '-5' to each side of the equation. 5 + -5 + 5x = 0 + -5 Combine like terms: 5 + -5 = 0 0 + 5x = 0 + -5 5x = 0 + -5 Combine like terms: 0 + -5 = -5 5x = -5 Divide each side by '5'. x = -1 Simplifying x = -1
| x^2-3y=17 | | 3(6x+2)=.5(4x+4) | | 4(3x-3)=3(4x-4) | | 3z+2(4x-2)=5(3-2) | | (8x^2-4x+14)+(-7x^2+3x-10)= | | 6x=2(4x+5) | | 3(4x+-5)=9 | | 3(4+-5)=9 | | 7c+-15=-2(6(c+-3)+-4(2+-1c)) | | 6x-3(2x-1)=6(-2+1)-3x | | 2x=180-7x | | 45=k(9)(5) | | -9p=-2 | | 4.9=7.3-0.6x | | a^2bc+ab^2c+abc^2=0 | | m^2+19m+48= | | X(x+81)=0 | | 8-2w^2=0 | | 5p-5q=-12 | | 4.9x+5=3.9x | | 10+8=-2(5x-9) | | 7x+9-6x=13 | | -20x=-4x-6 | | 2(x-3)=-h+3(h+6) | | 13-20= | | -14+1= | | v^2+2v-25=0 | | 2s^2=25 | | 150+110+450+x=1000 | | 4w+19=-7(w-9) | | X-6-25x^(1/2) | | 7+x+1=6x |